Enhanced enzymatic digestibility of mixed wood sawdust by lignin modification with naphthol derivatives during dilute acid pretreatment. (December 2018) - Lai, Chenhuan; Yang, Bo; He, Juan; Huang, Caoxing; Li, Xin; Song, Xiangyang; Yong, Qiang
Graphical abstract: Highlights: Lignin modification was performed by adding naphthol derivatives in the pretreatment. The addition of naphthol derivatives enhanced the enzymatic hydrolysis. 2-Naphthol-7-sulfonate was more effective than 2-naphthol. The enzyme non-productive binding was reduced with 2-naphthol-7-sulfonate addition. 2-Naphthol-7-sulfonate suppressed the lignin condensation during the pretreatment. Abstract: Effects of the addition of 2-naphthol and 2-naphthol-7-sulfonate on the dilute acid pretreatment of mixed wood sawdust were investigated, respectively. Compared to 2-naphthol, 2-naphtnol-7-sulfonate was more effective to enhance delignification and facilitate the enzymatic hydrolysis. The 72 h hydrolysis yield was improved by 47.8% for 2-naphthol-7-sulfone, while only 9.1% was observed for 2-naphthol. The surface charges, enzyme adsorption, and cellulose accessibility of dilute acid pretreated substrates with or without naphthol derivatives were examined. The improved enzymatic hydrolysis by adding 2-naphthol-7-sulfonate was ascribed to the higher negative surface charges, the lower enzyme non-productive binding, and the higher cellulose accessibility of pretreated substrates. Additionally, the HSQC NMR and 31 P NMR analysis were carried out on both decomposed lignins and residual bulk lignins. It indicated that the addition of the naphthol derivatives during pretreatment could suppress the lignin repolymerization, which further mitigated the inhibition of residual lignins on enzymatic hydrolysis.